#TITLE_ALTERNATIVE# - MURNIATI (NIM : 20212016) ; Pembimbing Prof. Dr.Eng. Mikrajuddin Abdullah, RIRI
A research has been conducted to analyze both qualitative and quantitative effect of TiO2 suspension presence in cigarette filter in order to make cigarette filter works maximum to reduce harmful substances present in cigarette smoke, optimizing the capability of TiO2 suspension as nanofilter in cigarette filters and reviewing the results of the analysis to obtain the results of the best variation. Samples in the form of filter paper that has passed of the smoke with some variation treatment as it become ready to be tested and analyzed. Parameter such as variations in the concentration of sample suspension of TiO2, TiO2 suspension volume variation, and the method of inputting the suspension of TiO2 into the cigarette filter. All samples were characterized using FT-IR spectrophotometer and the absorbance of all samples of the data obtained in each catchment area. The results showed that by reducing the percentage of the absorbance value of each catchment area, especially in the catchment area 1, 2 and 3 for the method of inputting the suspension of TiO2 through the cigarette filter tip and base, it appears that the most stable and lowest reduction present in samples C3 and H3, they are samples with a concentration of 1.85 mol / liter (2.5 g TiO2 + 10 ml distilled water) with a volume of 0.3 ml suspension. From the Lambert-Beer law we know that the absorbance value is proportional to the concentration of the sample, it means a low absorbance values will have dangerous compounds with smaller concentrations. Based on these results it appears that this sample has ability reducing the absorbance value thus also decreases the concentration of harmful substances in it. Samples C3 and H3 is reduced content of metallic elements significantly, but the method of inputting the suspension of TiO2 through a cigarette butt is better and safer than through the filter end of the cigarette.